Alternative carbohydrate use in relation protein:carbohydrate in performance and metabolism of pacamã (Lophiosilurus alexandri) - de Souza, Anderson Miranda; Figeuiredo, Rozzano Antonio Cavalcante Reis; Silva, Altiery Felix e; Melo, José Fernando Bibiano (Varia Scientia Agrárias, 2018)
We evaluated the inclusion of peeled-mango waste meal as source of carbohydrate in the protein:carbohydrate ratio (CP:CH) on performance and chemical composition of pacamã (Lophiosilurus alexandri) juveniles. One hundred and fifty fish (11.31 ± 0.96g) were stocked in sixteen 500 L tanks, fed three times daily (10% of live weight), in a system with water recirculation with biofilter. The treatments consisted of four experimental diets with decreasing levels of the ratio between crude protein and carbohydrate (1.40, 0.94, 0.56 and 0.29), with four replications per treatment. At the end of 60 days, we evaluated animal performance (average weight gain, specific growth rate, total apparent feed intake, carcass yield, survival) and metabolic parameters (glucose, cholesterol, triglycerides, plasma albumin and free total amino acids) and liver enzyme alanine aminotransferase activity (ALT). The protein:carbohydrate ratios affected all performance variables (p<0.05), except for survival. The values of metabolic variables have been changed from the increase of the ratio CP:CH (p<0.05), with the exception of cholesterol and plasma albumin. Mango meal be used in a relation of 1.38 CP:CH without harming the performance and metabolism.